Petrography and geochemistry of Tarkwaian quartzites at Amoanda Pit and banket conglomerates at saddle pit and their relationship with mafic intrusives in the area - Teye, Emmanuel Kofi (University of Mines & Technology, 2021)
Thin and polished sections of thirty-six rock samples from Amoanda Pit in the Tarkwaian showed that the banket footwall quartzites contain mainly quartz, chlorite, plagioclase, amphibole and minor sericite, epidote, chalcopyrite, pyrite, magnetite, hematite and trace gold. The protoliths of the rock were probably sublitharenite, feldspathic litharenite and litharenite. Overlying banket conglomerate at the Saddle Pit is oligomictic or polymictic with large rounded pebbles and moderately sorted quartz, chert, schist, and hornstone; the matrix is made up of quartz, plagioclase feldspars, sericite, chlorite, garnet and amphiboles. At the Saddle Pit, diorite sills and dykes contain mainly plagioclase feldspars, amphibole, chlorite, sericite and quartz with minor epidote, biotite, garnet, pyroxene, pyrite, pyrrhotite and chalcopyrite. Pyrite is partially altered to secondary hematite and magnetite. The intrusive heat might have introduced secondary amorphous gold other than the palaeoplacer granular gold in the banket footwall quartzite and the conglomerate. Post placer gold was secondary mainly at the contacts with diorite and associated with second generation hematite and magnetite. Generally the rocks were affected by greenshist facies metamorphism which post-date peak amphibolite facies. Whole rock XRF analyses show Al2O3 range from 6.86 to 26.6 wt% possibly due to plagioclase which is partially altered to sericite and quartz. Eu anomaly values are greater than 1 probably due to plagioclase accumulation while high total REE could be due to high alteration of the rocks.
x,105p; ill.
Keywords: Petrography; Geochemistry; Geology; Mining techniques